Simulação de emissões de misturas gasolina/etanol em motores de combustão interna - Juan Canellas Bosch Neto (2012)
This work was the development of computational algorithms for prediction of emissions in internal combustion engines from the coupling of the methodology of chemical equilibrium with the chemical kinetics. Mathematical modeling of chemical equilibrium methodology was based on mass balances and equilibrium relationships generating a non-linear system with twenty-two and twenty-two unknowns equations solved by the Newton-Raphson method. It was possible to calculate the concentrations of twenty-one chemical species generated in the combustion of various fuels, fuel blends, such as gasoline and ethanol, for a given pressure,temperature and fuel / air ratio. To solve the numerical method of Newton-Raphson was necessary that the initial estimatives were always close to the solution, so there would guarantee the convergence of the system. Thus it was necessary to perform a procedure in which the solutions obtained feed initial estimates of the routines. The algorithm was implemented in the MATLAB software, version 7.4, having as inputs the temperature, the relative air / fuel, the pressure in the combustion chamber and the fuel type (formula minimum fuel). The outputs of the routine concentrations were twenty-one species generated in the combustion reaction and the number of moles thereof. After the development of routine chemical equilibrium was performed with a coupling routine chemical kinetics for predicting species having a slow kinetic, such as nitrogen and carbon monoxide. We used six equations for predicting species by chemical kinetics three of them belonging to theZeldovich mechanism. A simulation program was developed engines from the coupling of equilibrium methodology to the methodology of chemical kinetics. The program needs data from the pressure curves of the engine temperature and relative fuel / air versus crankshaft angle. As the crank angle advances in small steps, it has been the method of compositions where the derivatives calculated, stored and subsequently integrated by the Runge-Kutta method. Generating a series of simulations and one of them was compared to the results ofexperiments in the literature in a bank of internal combustion engines. Was developed a routine for predicting uncoupled hydrocarbon openings formed in the combustion chamber. The results obtained in the simulation were similar to the values found in the experimentaldata. The difference of this work in relation to the works commonly found in the literature is that it directly engages the methodology of chemical equilibrium with the methodology of chemical kinetics and reduced subsequent numerical integration of the system of nonlinear differential equations, obtaining a result of computer simulation with robustness, better convergence and faster calculation that similar software.